2015
DOI: 10.1007/s40565-015-0135-x
|View full text |Cite
|
Sign up to set email alerts
|

Compensating active power imbalances in power system with large-scale wind power penetration

Abstract: Large-scale wind power penetration can affect the supply continuity in the power system. This is a matter of high priority to investigate, as more regulating reserves and specified control strategies for generation control are required in the future power system with even more high wind power penetration. This paper evaluates the impact of large-scale wind power integration on future power systems. An active power balance control methodology is used for compensating the power imbalances between the demand and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…A WTG possesses a significant amount of kinetic energy in the rotating masses, which can be utilized to provide a short-term frequency support in the event of large power imbalance [76]. In general, wind turbines can be divided into two main groups: fixed-speed WTs (FSWT) and variable-speed WTs (VSWT).…”
Section: Frequency Regulation Performance Comparison Of Different Typmentioning
confidence: 99%
“…A WTG possesses a significant amount of kinetic energy in the rotating masses, which can be utilized to provide a short-term frequency support in the event of large power imbalance [76]. In general, wind turbines can be divided into two main groups: fixed-speed WTs (FSWT) and variable-speed WTs (VSWT).…”
Section: Frequency Regulation Performance Comparison Of Different Typmentioning
confidence: 99%
“…In current power system operations, conventional power plants are responsible for providing system services, while renewable generation sources (WPPs) are exempted for providing the required support [1,3,24,25]. Studies have shown that WPPs can also contribute actively to power balancing control [4,5,26].…”
Section: System Modelingmentioning
confidence: 99%
“…Moreover, this research work also compared the aforementioned case with cases when WPP was not contributing to system ancillary services. The results were taken from the previous study carried out by [3]. The active power balance was achieved by CHP only, and WPP was always operating at the maximum.…”
Section: Case Study 1: Power Balance Control Through Wpps and Chpsmentioning
confidence: 99%
See 2 more Smart Citations